Ulema's Business Strategy in Indonesia: A Study Case - Zainal Abidin; Ahmad Ajib Ridlwan (al-Uqud : Journal of Islamic Economics, 2021)
The role of ulema in the life of the Madurese community is not only as a religious leader but also as an advisor in all aspects of life, e.g., marriage, childbirth, aqiqah, and death. In addition, ulema also plays a role in the development of community business, as has been done by several ulemas in Madura, such as one of the caregivers of the most prominent Islamic boarding school in Madura. This study aims to analyse the business strategy of Madurese ulama. It is qualitative research with in-depth interviews about the business strategy developed by ulema in Madura. Four Islamic boarding schools and ulema are the objects of this research, so this research concludes that the ulema in Madura do not have a specific business strategy. However, observing the business practices carried out by the Madurese ulama, the ulema has implemented a business strategy, namely a product differentiation strategy. Product differentiation strategy is a competitive strategy that refers to different customer perceptions of the same product. Thus, all business areas cultivated by ulema will be developed on the condition that they do not conflict with Islamic teachings.